The odyssey - Homer (Penguin active reading, 2008)
This book tells the story of the great hero Odysseus who has been away from his family for twenty years when the goddess Athene decides to help him find his way back to the island of Ithaca. But the journey will not be easy. Odysseus must face storms, monsters and the terrible anger of the sea-god Poseidon. And if he succeeds, will he be welcomed home?